The Relationship Between The Quality Of The Online Registration System And The Satisfaction Level Of Outpatient Patients - Santhosa, Pande Wayan; Purwanti, Ika Setya; Subhaktiyasa, Putu Gede (Jurnal EduHealth, 2024)
The conventional patient registration system has evolved into an online platform utilizing information technology. However, the use of online registration systems still faces issues that affect patient satisfaction. Bangli General Hospital has implemented an Online Registration System (SIDOLI), but patient satisfaction with this system has not yet been evaluated. This study aims to determine the relationship between the quality of the online registration system and the satisfaction level of outpatient patients at Bangli General Hospital.This study uses a quantitative approach with a cross-sectional design. The research was conducted in April 2024 with a sample of 70 outpatients using the SIDOLI online registration system, determined through purposive sampling techniques. The results of the study show that 55.7% of respondents rated the quality of SIDOLI as good, 32.9% as adequate, and 11.4% as poor. The patient satisfaction level showed that 55.7% were satisfied, and 32.9% were dissatisfied. The chi-square test results indicate a significant relationship between the quality of the SIDOLI online system and outpatient satisfaction at Bangli General Hospital (p = 0.05), with a weak correlation (r = 0.279). Improving the quality of the online registration system tends to increase patient satisfaction, although this increase is relatively weak. The results of the study provide comprehensive insights into the development and evaluation of online systems in healthcare services.